Evaluating 'good governance': The development of a quantitative tool in the Greater Serengeti Ecosystem. (1st October 2016) - Kisingo, Alex; Rollins, Rick; Murray, Grant; Dearden, Phil; Clarke, Marlea
Abstract: Protected areas (PAs) can provide important benefits to conservation and to communities. A key factor in the effective delivery of these benefits is the role of governance. There has been a growth in research developing frameworks to evaluate 'good' PA governance, usually drawing on a set of principles that are associated with groups of indicators. In contrast to dominant qualitative approaches, this paper describes the development of a quantitative method for measuring effectiveness of protected area governance, as perceived by stakeholders in the Greater Serengeti Ecosystem in Tanzania. The research developed a quantitative method for developing effectiveness measures of PA governance, using a set of 65 statements related to governance principles developed from a literature review. The instrument was administered to 389 individuals from communities located near PAs in the Greater Serengeti Ecosystem. The results of a factor analysis suggest that statements load onto 10 factors that demonstrate high psychometric validity as measured by factor loadings, explained variance, and Cronbach's alpha reliability. The ten common factors that were extracted were: 1) legitimacy, 2) transparency and accountability, 3) responsiveness, 4) fairness, 5) participation, 6) ecosystem based management (EBM) and connectivity, 7) resilience, 8) achievements, 9) consensus orientation, and 10) power. The paper concludes that quantitative surveys can be used to evaluate governance of protected areas from a community-level perspective. Highlights: Key to the effective delivery of Protected Area benefits is the role of governance. Measuring effectiveness of protected area governance is challenging. Community perceptions of governance were measured in the Tanzanian Serengeti. Perceived governance effectiveness was measured with a quantitative questionnaire. Governance statements loaded onto 10 factors with high psychometric validity.